2019
DOI: 10.1002/ejic.201900627
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Investigation of the Thermal Decomposition of Cl4(CH3CN)W(NiPr) During Simulated Chemical Vapor Deposition

Abstract: Design of precursors for thin film growth by chemical vapor deposition (CVD) can be informed by knowledge of the precursor decomposition mechanism. However, the vast majority of decomposition characterization is done by techniques that do not capture CVD conditions. This work used a custom CVD reactor with in situ Raman spectroscopy capabilities to investigate the gas phase thermal decomposition of the tungsten imido complex Cl4(CH3CN)WNiPr, a known precursor for the aerosol‐assisted (AA)CVD of tungsten carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…For example, in situ UV spectroscopic or FTIR exhaust gas studies have been used to establish chemical reactions paths in the CVD of gallium nitride (GaN) films, 21,22 and gas chromatography coupled with mass-spectrometry (GC-MS) was applied to investigate the thermal decomposition and by-products generation in CVD of titanium nitride (TiN) films. 23 More recent implementations involve in situ Raman spectroscopy during thermal decomposition of a tungsten imido complex by aerosol-assisted (AA)CVD, 24 or in situ optical emission spectroscopy during microwave plasma-enhanced chemical vapor deposition of phosphorus (P) and nitrogen (N) co-doped nanocrystalline diamond. 25 Focusing on analogous studies of CVD processes involving silicon-containing precursors, the majority of the reported 6 literature concerns the binary systems SiC, SiO2 or Si3N4 from chlorosilanes, silanes or TEOS.…”
mentioning
confidence: 99%
“…For example, in situ UV spectroscopic or FTIR exhaust gas studies have been used to establish chemical reactions paths in the CVD of gallium nitride (GaN) films, 21,22 and gas chromatography coupled with mass-spectrometry (GC-MS) was applied to investigate the thermal decomposition and by-products generation in CVD of titanium nitride (TiN) films. 23 More recent implementations involve in situ Raman spectroscopy during thermal decomposition of a tungsten imido complex by aerosol-assisted (AA)CVD, 24 or in situ optical emission spectroscopy during microwave plasma-enhanced chemical vapor deposition of phosphorus (P) and nitrogen (N) co-doped nanocrystalline diamond. 25 Focusing on analogous studies of CVD processes involving silicon-containing precursors, the majority of the reported 6 literature concerns the binary systems SiC, SiO2 or Si3N4 from chlorosilanes, silanes or TEOS.…”
mentioning
confidence: 99%
“…Examples of such mechanistic studies are presented in this Perspective. It is also important to obtain data during deposition using techniques such as RGA of reactor effluent or in situ spectroscopy of gas-phase species generated from simulated or real CVD. , …”
Section: Discussionmentioning
confidence: 99%
“…It is also important to obtain data during deposition using techniques such as RGA of reactor effluent or in situ spectroscopy of gas-phase species generated from simulated or real CVD. 100,101 Traditional CVD remains a standard technique for synthesizing high-quality conformal thin films for numerous applications, but the requirement of precursor volatility for traditional CVD imposes a limitation on the precursors that can be used. AACVD offers the advantage of avoiding the volatility requirement, which allows for greater freedom in designing precursors.…”
Section: ■ Conclusionmentioning
confidence: 99%